(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2024)
• You love animals, you are like your grandfather. When talking about a village, of course, you will say camel or mare. Why? Being busy with them is interesting, as they love you too, know you, and understand what you say. Only they can not talk. When I was young, I used to have Donan. He was my friend, we grew up together, and I welcomed a newborn guest with my mother. Being born, he stared at me, his thin legs were shaking. His legs` ankle was spotted, and on his forehead there was a white spot. His eyes were as big and beautiful as deer`s. my grandfather said that he was mine. I took care of him when he was growing up. He would not eat anything if someone gave instead, also he urged me to go to the water. We used to go to the middle ditch together; he did not want to drink water from that ditch. Then we went to Toshloq. He used to drink from Toshloq. I washed him for a long time.